Aspirin for thromboembolic complication prevention in cardiovascular disease: dose optimization and adverse effect minimization - A. N. Britov (Кардиоваскулярная терапия и профилактика, 2006)
The review is devoted to acetylsalicylic acid (ASC) use in cardiology. Recent epidemiologic surveys demonstrated the important role of thrombosis as a factor provoking exacerbation of coronary heart disease, ischemic stroke, peripheral artery disease. Therefore, antithrombotic and antiplatelet therapy becomes most important in treating these diseases and in secondary prevention of vascular occlusion. Numerous studies proved that ASC therapy (75-325 mg/d) decreases risk of myocardial infarction, stroke, and cardiovascular mortality by approximately 25%. The review also contains the results of most reliable ACS trials, and comparison of ACS therapy with other antiplatelet regimens. An emphasis is put on ASC therapy safety. A relatively new medication, Cardiomagnyl, is described – a combination of ASC and non-absorbing antacid, Mg hydrate. This combination minimizes the risk of gastro-intestinal complications, including hemorrhage and perforation.